Evaluation of the Pancreatoprotective Effect of Nannochloropsis oculata Extract against Streptozotocin-Induced Diabetes in Rats - Wael Mahmoud Aboulthana, Amal Mohamed El-Feky, Noha El-Sayed Ibrahim, Ram Kumar Sahu, Abo El-Khair Badawy El-Sayed (Journal of Applied Pharmaceutical Science, 2018)
Diabetes mellitus is a chronic degenerative disease. In the developed countries, it is considered as the third leading cause of death following heart and cancer diseases. The most effective algal extract was prepared from Nannochloropsis oculata to treat diabetes-induced by Streptozotocin (STZ). In the present study, STZ showed a significant (P < 0.05) increase in glucose and C-reactive protein (CRP) levels associated with a decline in insulin level. This was parallel to histopathological alterations in the pancreas of diabetic rats. The N. oculata algal extract lowered glucose and CRP levels significant (P Ë‚ 0.05) with restoring the insulin level to normalcy. The electrophoretic protein and lipoprotein patterns showed that STZ caused the disappearance of several normal bands. The α-amylase and α-esterase (EST) were expressed severely and represented as one thick band in the diabetic group. Also, STZ caused qualitative alterations in the arrangement of the bands of β-EST pattern. The algal extract decreased the quantity of α-amylase and α-EST bands and restored the normal β-EST bands. Furthermore, STZ decreased the number of the bands in the electrophoretic catalase (CAT) and peroxidase (POX) patterns associated with the existence of abnormal bands. The algal extract restored the normal bands with hiding the abnormal ones. STZ induced cleavage of the genomic DNA leading to the existence of several unique bands. The algal extract maintained the integrity of the genomic DNA. The study concluded that algal extract showed an ameliorative effect against diabetes induced by STZ at biochemical, histopathological and molecular levels in the pancreas of rats.
Keywords: Diabetes mellitus, Nannochloropsis oculata, Electrophoresis, Isoenzymes, Genomic DNA.